Scattering times and surface conductivity of Dirac fermions in a 3D topological insulator film with localised impurities. (24th September 2015) - Sengupta, Parijat; Bellotti, Enrico
Abstract: The zero gap surface states of a 3D-topological insulator host highly mobile Dirac fermions with spin locked to the momentum. The high mobility attributed to the absence of back scattering is reduced in the presence of impurities on the surface. In particular, we discuss and compare scattering times for localised impurities on the surface, scattering between states of opposite helicity located on different surfaces coupled through a hybridisation potential and the role of magnetic impurities. Magnetic impurities give rise to an additional spin suppression factor. The role of warped bands and their influence on topological factors that can enhance the overall surface mobility is examined. Finally, employing a linearised Boltzmann equation approach, surface conductivity calculations for Dirac fermions in a 3D TI is outlined.